HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU REMAJA PUTRI TENTANG PERSONAL HYGIENE DI DESA BARO YAMAN KABUPATEN PIDIE - Evi Kurniawati; Afriana; Roza Aryani (Rena Cipta Mandiri, 2025)
Improper personal hygiene during menstruation carries the risk of reproductive tract infections, one of which is vaginal discharge. Untreated vaginal discharge can lead to serious problems for women, such as infertility, ectopic pregnancy, pelvic inflammatory disease, and chronic pelvic pain. A preliminary survey found that most adolescent girls do not understand how to properly care for their reproductive organs during menstruation. The purpose of this study was to determine the relationship between knowledge and attitudes and the behavior of adolescent girls regarding personal hygiene in Baro Yaman Village, Mutiara District, Pidie Regency in 2025. This research method was analytical with a cross-sectional approach. A total sample of 43 adolescent girls was taken from the total population. The study was conducted from July 3-16, 2025. Data were processed using univariate and bivariate analyses using the Chi-square test. The results showed a relationship between knowledge and attitudes and adolescent girls' behavior regarding personal hygiene, with a ρ value of 0.001. It is hoped that the results of this study will improve adolescent girls' understanding of personal hygiene during menstruation, thereby improving their reproductive health.